Dialogues of sexualities: An action research project - Graham, Nicola Susan Jearey (Rhodes University, Faculty of Humanities, Department of Psychology, 2016)
Risky and abusive sexual behaviours, stemming largely from inequitable gendered norms, are a pervasive feature of the South African socio-sexual landscape. Literature shows that sexuality education programmes can be effective in reducing risky sexual practices, but South African school sexuality education has been shown to be largely inadequate. The question arises as to how to engage with high school learners about sexualities in meaningful ways. In an attempt to answer this, I implemented a dialogical sexuality action research project at a lower middle class urban high school. Freirian principles of critical consciousness and dialogical pedagogy were utilized, and these were infused with feminist post-structural understandings of a discursively constituted subject. The initial consultative process started in 2012 with two projects at the school. Data from these projects, and a further consultation with the school principal, provided baseline information on the gendered norms and the sexuality education in the school. I then instituted a dialogical sexuality intervention with a group of Grade 10 learners, aiming to bring gendered and sexual norms to visibility, to trouble them (thereby promoting participants' critical consciousness around gendered norms), and to provide recognition for participants in a variety of subject positions. Ten sessions were conducted, with the focus of each session being planned by the group. The action research project attempted to promote understandings of the processes required to facilitate such aims. The dialogical format of the group generated curiosity and engagement, and there were suggestions that some participants were taking up safe-sex messages in a reflexive manner. A partial normalisation of some 'hidden' aspects of sex, particularly around issues pertaining to female sexuality, was enabled, and critical consciousness around the gendered inequities in 'cheating' was promoted. However, abstinence was relatively silenced, and male same-sex remained heavily stigmatised. No substantial action component beyond the group meetings was generated. Participant feedback indicated that they placed great value on the dialogical processes in the group, and that they enjoyed being able to talk about sexual and other personal aspects of their lives. I theorise that the value of the group was in the recognition that participants received as they were positioned in a variety of subject positions. Whilst dialogue was shown to be extremely valuable, there were suggestions that other, non-dialogical modes of recognition were also needed by participants.
Keywords: Uncatalogued